Modern concepts of interaction with consumers in the FMCG sector - Kim, И.А.; Akhmetova, З.Б. (Journal of Economic Research & Business Administration, 2023)
The scientific article thoroughly analyzes contemporary consumer engagement strategies within the FMCG sector, exploring innovative methods by leading brands to connect with their target audience and enhance sales performance through developing consumer-brand relationships. The primary aim of this research is to scrutinize the current state of consumer engagement in the dynamic FMCG sector. The study employs a multifaceted methodology to emphasize the sector's need to adapt to evolving consumer behaviors. This includes extensive desk research, expert interviews, and retail audits to delve into modern consumer engagement concepts. Expert interviews with 40 FMCG professionals specializing in demand management, marketing, sales, or retail constitute the primary research. Quantitative survey data underwent statistical analysis, while qualitative information was extracted through thematic analysis. The study also incorporates a cross-sectional analysis and audit of retail trade in Kazakhstan, utilizing structured checklists, questionnaires, and observation protocols to assess implementation and effectiveness, aligning with expert opinions. The study identifies "Ideal Store" and "Omnichannel Communications Strategy" as pivotal concepts, emphasizing the importance of in-store interaction and digital technologies. Key elements such as product visibility and loyalty programs are deemed crucial, with sustainability ranking lower. A Kazakhstan retail audit pinpoints challenges in product placement, technology integration, and loyalty programs, underscoring the imperative for improvement. Recommendations stress exploring customer-centric approaches and the strategic use of digital technologies to enhance consumer engagement in the FMCG sector. This study significantly contributes to comprehending consumer engagement strategies in the FMCG sector, offering practical insights for FMCG companies to enhance consumer interaction, bolster brand loyalty, and optimize sales efficiency. The proposed innovative approaches can fortify market positions and ensure sustainable growth in an industry marked by continual change. Key words: consumer interaction; retail strategy; multi-channel strategy; personalization; purchase process; marketing integration; data analysis.